Integrative exercises system to favor the Chemistry abilities in Unit No. 2 “The metallic hydroxides” in Junior High School Education (Original) (REDEL. Revista Granmense de Desarrollo Local, 2019)
The present work shows the results of the investigation carried out in Junior High School Education, to favor the learning of Chemistry at that level throughout the realization of an exercises system according to the levels of cognitive performance considering a theoretical and practical conception in the contents of the metallic hydroxides. This paper responds to a present-day problem related to teaching learning process in Cuba. The system has been applied in educative.
Keywords: ability; learning developer; focus interdisciplinar; metallic hydroxides